CHEMISTRY IN COLLEGE−LEVEL ENVIRONMRNTAL SCIENCE CURRICULA - Henry A. Alegria; Lembit Nei (European Scientific Journal, ESJ, 2014)
Insufficient proportion of chemistry classes in most of the collegelevel environmental science curricula is mostly ignored by the relevant scientific publications. Graduates of environmental science programs are often very weak in their understanding of the principles from chemistry underlying environmental science. The need for a stronger environmental chemistry component to be part of environmental science curricula is evident. The role of chemistry as an essential basis for environmental education should find much more attention in the relevant scientific literature.